Etika Pelanggan Dalam Memberikan Respone Terhadap Penyajian Makanan Di Hub D'raja Coffee - Defhany; Rachel Mia L. Lbn. Toruan; Evi Enitari Napitupulu; Open Berkat (Universitas Sari Mutiara Indonesia, 2023)
This study aims to analyze Customer Ethics in responding to food presentation at HUB D’Raja Coffee. The study emphasizes a qualitative approach with descriptive methods. The results of the study indicate that in carrying out the service provided by cafe waiters to customers, they always refer to the SOP that has been given by the owner and always adhere to three principles, namely Greeting, Smiling and greeting customers, both regular customers who often visit D’Raja and new customers who do not know about the cafe at all. This is inseparable from how employees or staff respond to what customers will order by using data management techniques, sources and methods accrding to the validity of the data they have.